The European debt crisis and the US economy. (1st January 2013) - Sheehan, Patrick
The European debt crisis has been a growing concern for many countries since 2010. European leaders and institutions have formulated unprecedented packages of emergency funding to deteriorate the rising financial market tensions that stemmed from the fiscal solvency of Greece and other Eurozone nations. As a result, many economists are uncertain about the future of the Eurozone and the contagion effect it could have on many developed and developing economies. Being strongly correlated with Europe, the USA is one of the vulnerable economies that could be affected by the overbearing financial problems. Having just left an economic recession, the US economy must be aware of the issues and concerns overseas and understand that a strengthening crisis could ultimately have an adverse effect on the economy, ultimately pushing the US back into an economic recession.